MAXWELL'S EQUATIONS AND ELECTROMAGNETIC WAVES: SHAPING MODERN TECHNOLOGY - Winarni, Kiki Ayu; Febrianti, Tanti; Putra, Gede Mudita Edi; Akhsan, Hamdi; Ismet, Ismet (EduFisika: Jurnal Pendidikan Fisika, 2025)
This meta-analysis investigated how Maxwell's Equations and electromagnetic waves shaped key advances in modern technology. A systematic review was conducted across major academic databases, initially identifying 150 otential sources. Applying predefined inclusion criteria, findings were synthesized from 30 included studies. This synthesis revealed that these foundational concepts shaped technological advancement by providing the essential theoretical framework for understanding electromagnetic wave generation, propagation, and interaction with matter. This understanding was found to be pivotal in enabling breakthroughs across diverse domains identified in the synthesized literature, including Wireless Communication, Microwave Technology, Medical Imaging, Renewable Energy, and Metamaterials, among other related fields. This synthesis provides a comprehensive perspective on the mechanisms by which fundamental electromagnetic theory underpins technological progress. The findings underscore the enduring practical relevance of Maxwell's Equations and electromagnetic waves for research and engineering and offer valuable material for physics education by demonstrating their tangible impact in shaping the modern world.